OPPORTUNITIES FOR THE DEVELOPMENT OF INTERNATIONAL TOURISM USING NATIONAL TRADITIONS AND CUSTOMS (Analysis of International Sciences, 2024)
Today in the day tourism industry high to indicators have being is going in Uzbekistan of tourism 3 main types available : input, output and internal tourism . Enter and internal to tourism main and special touristic products includes : touristic attention deserves to places excursions ; hotels, rest residences, spas, sanatoriums, tourism villages, home-camps, camps placement ; national dishes and wines taste to see festivals and holiday in events participation reach country across comfortable action